One new genus and one new subgenus of the tribe Lamiini (Coleoptera: Cerambycidae: Lamiinae) from Asia - Bi, Wen-Xuan; Chen, Chang-Chin; Lin, Mei-Ying (Zootaxa, 2024)
The genus Mecynippus Bates, 1884 is investigated and considered a monotypic genus. Falsomecynippus Bi, Chen & Lin, gen. nov., is established for Monohammus ciliatus Gahan, 1888 which was previously placed in Mecynippus. One new subgenus is described based on Falsomecynippus (Tuberculhammus) superbus Bi, Chen & Lin, subgen. nov. & sp. nov. from China and Laos. Illustrations of the habitus, endophallic structures, and major diagnostic features for all involved taxa are provided.